CAMPUS AMBASSADOR STRATEGY ANALYSIS OF BRAND IMAGE AT MEZINK INDONESIA - Putri Citta Nathania; Cecep Safa'atul Barkah (Jurnal Ilmu Administrasi Bisnis, 2024)
In the growing digital and connectivity era, the role of Brand Ambassadors in influencing brand image is becoming increasingly significant. A comprehensive analysis of Campus Ambassador's brand image strategy is important to understand how the use of this strategy can shape consumer perception. This study attempts to evaluate the degree to which Campus Ambassador influenced Mezink Indonesia's brand image. This paper was written using a descriptive qualitative technique. In addition, to support this research, a SWOT analysis was carried out so that researchers know the right strategy for the company. Analysis of Campus Ambassador's strategy on brand image at Mezink Indonesia shows that the use of Campus Ambassador can be an effective method to build and strengthen brand image among students.Keywords: Brand Ambassador, Brand Image, SWOT Analysis